A "Delphi Exercise" as a Tool in Amazon Rainforest Valuation - Strand, Jon (World Bank Group, Washington, DC, 2015)
The Amazon rainforest, the world's largest and most biodiverse, represents a global public good of which 15 percent has already been lost. The worldwide value of preserving the remaining forest is today unknown. A "Delphi" exercise was conducted involving more than 200 environmental valuation experts from 36 countries, who were asked to predict the outcome of a survey to elicit willingness to pay for Amazon forest preservation among their own countries' populations. Expert judgments of average willingness-to-pay levels, per household per year, to fund a plan to protect all of the current Amazon rainforest up to 2050, range from $4 to $36 in 12 Asian countries, to near $100 in Canada, Germany, and Norway, with other high-income countries in between. Somewhat lower willingness-to-pay values were found for a less strict plan that allows a 12 percent further rainforest area reduction. The elasticity of experts' willingness-to-pay assessments with respect to own-country per capita income is slightly below but not significantly different from unity when results are pooled across countries and income is adjusted for purchasing power parity.